x2 + 36 = 20x
so x2 - 20x + 36 = 0
so x2 - 2x - 18x + 36 = 0 or x(x - 2) - 18(x - 2) = 0
that is (x - 2)(x - 18) = 0 so x - 2 = 0 or x - 18 = 0 ie x = 2 or x = 18
Chat with our AI personalities
x2 + 20x +0 =30 [(20/2)2 =100] x2 + 20x + 100 =30 +100 √(x+10)2=√130 x+10=√130 x= −10+√130 √ means square root
x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7
x2 + 13x + 36 = (x + 9)(x + 4)
10x2 - 64 = 36 + 6x2; whence, 4x2 - 100 = 0, x2 = 25, and x = ±5.
f(x1) = (-5)2 + 3*(-5) + 5.1 = 25 - 15 + 5.1 = 15.1 f(x2) = (6)2 + 3*(6) + 5.1 = 36 + 18 + 5.1 = 59.1 f(x2)-f(x1) = 59.1 - 15.1 = 44 x2 - x1 = 6 - (-5) = 11 So average rate of change = 44/11 = 4